Pengembangan Lembar Kerja Peserta Didik Pembelajaran Lompat Jauh Gaya Menggantung Menggunakan Pendekatan Problem-Based Learnig: Developing Students Worksheet of Hanging Style Long Jump Learning Using The Problem-Based Learning Approach - Listiono, Bernaditya; Winarni, Sri (Pedagogia : Jurnal Pendidikan, 2019)
The purpose of this study was to describe the development LKPD with PBL approach that is valid and practical. This study used the research method of developing a 4D model with test subjects in class X APHP 1 and X APL 1 at SMK N 1 Cangkringan, Sleman. The results of the teacher's practicality assessment after the LKPD applied in long jump learning in both classes met the practicality criteria with a very good category. The per- centage of students' practicality assessment of LKPD with a minimum category both in both classes fulfilled more than 80%. In class X APHP 1 as many as 100% of students stated that LKPD in the minimum category was good and in class X APL 1 as many as 93.55%. Thus LKPD hanging style long jump learning with PBL approach can be said to be valid and practical.